Czar rewii. Nowoczesne oblicze teatru robotniczego Erwina Piscatora - Wąsik-Linder, Monika (Śląskie Studia Polonistyczne, 2020)
The article is devoted to the phenomenon of political revue, which in the 1920s became a form of political propaganda in Germany. Erwin Piscator’s revue RRR described here is a good example of its agitprop success. Piscator used the revue (which had been associated with bourgeois entertainment until then) for revolutionary goals, appreciating its form primarily for its huge staging potential. The open form of the revue enabled him to combine different genres and contrasting threads, and exploited the new technologies of the time, including the new media (film, photography, radio). Another interesting point is that for Piscator the revue was the future of modern theatre – not only agitprop theatre, but theatre in general.